Can radiotherapy be omitted in T1-2N1 breast cancer patients after mastectomy without neoadjuvant therapy? - Hou, Jing; Qian, Shuangqiang; Liao, Chenyi; Wu, Chengwen; Zhang, Xi; Gao, Yanchun (Frontiers in Oncology, 2026)
ObjectiveTo evaluate the necessity of postmastectomy radiotherapy (PMRT) in patients with T1-2N1M0 breast cancer who did not receive neoadjuvant therapy, by assessing its impact on locoregional recurrence (LRR) and overall survival (OS) in the context of contemporary systemic therapies. This meta-analysis aims to provide updated evidence on whether PMRT can be omitted in this specific population.MethodsStatistical analysis was conducted using Review Manager version 5.4 software, as recommended by the Cochrane Collaboration. HR for LRR and OS were pooled between the PMRT and no-PMRT groups. A fixed-effects model was primarily used, with a random-effects model applied if heterogeneity (I² > 50%) was detected. Bias risk in the included studies was assessed using the Newcastle-Ottawa Scale, and publication bias was evaluated through funnel plot analysis.ResultsIn patients with T1-2N1M0 breast cancer, PMRT significantly reduced the risk of LRR (pooled HR = 0.35, 95% CI: 0.23–0.53; p<0.001) and improved OS (pooled HR = 0.65, 95% CI: 0.61–0.69; p<0.001). Subgroup analyses showed consistent benefit for LRR reduction at 5 years (HR = 0.45, 95% CI: 0.35–0.56) and 10 years (HR = 0.33, 95% CI: 0.19–0.57; interaction p=0.33). For OS, a significant 5-year survival improvement was observed (HR = 0.63, 95% CI: 0.59–0.67; p<0.001), but the 10-year benefit was non-significant (HR = 0.80, 95% CI: 0.60–1.07; p=0.14).ConclusionsThis meta-analysis supports the use of postmastectomy radiotherapy in T1-2N1M0 breast cancer patients, demonstrating its significant reduction in LRR and improvement in OS. Future research should integrate molecular subtypes and dynamic risk models to optimize treatment decisions within contemporary systemic therapy frameworks, and prospective studies are needed to assess the long-term safety of PMRT omission in certain subgroups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420261287168, identifier CRD420261287168.